Individualized care for patients with intersex (differences of sex development): part 4/5.Considering the Ifs, Whens, and Whats regarding sexual-reproductive system surgery. Issue 3 (June 2021) - Bangalore Krishna, Kanthi; Kogan, Barry A.; Mazur, Tom; Hoebeke, Piet; Bogaert, Guy; Lee, Peter A.
Summary: Issues and concerns regarding surgery of the sexual-reproductive anatomy during infancy and early childhood are discussed using four actual examples. A case of a 46, XX infant with 21 hydroxylase deficiency congenital adrenal hyperplasia (CAH) with atypical (ambiguous) genitalia is discussed regarding timing and potential harms and benefits of surgery. We present the perspective of balancing the child's rights to bodily autonomy and right to an open future versus parents' decision making authority regarding what they perceive as their child's future best interests. The second case is a newborn with complete androgen insensitivity syndrome and we discuss the harms, benefits and timing of gonadectomy. The third case examines the physical and psychological impact of penile shaft hypospadias, raising the question of whether surgery is justified to prevent what may or may not be considered a permanent disability. The fourth case involves an adult woman with classic CAH, born with a urogenital sinus and clitoromegaly, who never had genital surgery and is now requesting vaginoplasty, but not clitoral reduction. The primary message of this article, as the previous articles in this series, is to encourage patient-family centered care that individualizes treatment guided by shared decision making.